The Public-Private Partnership in the infrastructure of the Netherlands and the Czech Republic - Procházková, Alena; Mejzlík, Ladislav, 1961-; Zwerk, Danny; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2012)
In the Czech Republic, half of the infrastructure network is still missing. Moreover, in the past, Dutch and Czech road infrastructure projects have been delivered over-budget and rarely on schedule. Despite a weak fiscal position in the Czech Republic there is still a need for infrastructure investments. Solution for mentioned issues can become the realization of the Public-Private Partnership (PPP) projects. The features (for instance the payment mechanism) of Public-Private Partnership (PPP) projects not only make these investments possible but also solve other problems mentioned. Both the Netherlands (NL) and the Czech Republic (CR) have already established an environment enabling PPP implementation (e.g. established PPP Units, methodologies, dealing with legislation); But despite many PPP projects being carried out on the municipality level, there is not even one PPP project being implemented on the national level in the CR. This is in contrast to the NL, where there is already a developed PPP market, and there is investment in several new national projects every year. How can the CR improve its PPP implementation policy? The answer to this question provides the final recommendations based on the Dutch PPP practice within this Master's thesis. Learning from mistakes of the other countries, in this case it is the Netherlands, may provide for higher effectiveness in the PPP implementation and in the faster adaptation or improvement of the current partnerships. To elaborate the thesis it has been used interviews, questionnaire and several primary and secondary sources, that have been available in czech, dutch and english languages.
The main contributors to the development of this thesis have been the experts from the Dutch PPP Unit at Ministry of Infrastructure and Environment and the experts from the UNECE, who commented on the results and enabled application of the UN National PPP Readiness Self-Assessment tool to enhance the quality of the thesis. Other contributors are experts from PPP Centre at Ministry of Finance of the Czech Republic, PPP Association, Czech Ministry of Transport and Ministry of Finance. The tools, recommendations, as well as the PPP maturity Pyramid occurring within the Master's thesis can be applied not only for the further development of the PPP implementation in the Czech Republic, but also in other Eastern European countries. General recommendations arose by comparing practices of both the CR and the NL with respect to the UNECE's criteria. The all recommendations have been shown for clarity in terms of political, practical and procurement level. This comparison has practically enabled to point out the strengths and weaknesses of PPP projects in the CR and NL. Dutch experience has served as a source of considerable information that can make the practical implementation of Czech PPP projects much easier. As a part of the final conclusions of the thesis can be considered a PPP Maturity Pyramid, which schematically describes the current position of both countries due to the successful use of PPP projects. Basically, both countries have already passed "Bad" experience with PPP projects, have produced suitable environment and conditions for their use, but the next step is very important for the successful implementation of PPP projects in the CR. Based on the political support (considered as an essential factor), it is necessary to learn from the past mistakes and start with the practical realization of simple projects (from the beginning) that can be the basis for a standardization and a practical application of PPP projects in the future.
Vedoucí práce: Ladislav Mejzlík
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: účetnictví a finanční řízení podniku [obor dipl. práce]; diplomové práce; master's theses